Separator for secondary battery and electrochemical element comprising same
By forming a porous substrate and an inorganic particle layer on the ceramic coated separator, and adding organic particles with specific forms to form an adhesive layer, the problem of insufficient adhesion between the ceramic coated separator and the electrode is solved, and excellent electrodes are achieved Adhesion, anti-adhesion and breathability ensure the stability and safety of the battery.
Patent Information
- Application Number
- CN202420542420.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-20
- Filing Date
- 2024-03-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2034-03-20
AI Technical Summary
The adhesion between the existing ceramic-coated separator and electrode is insufficient, resulting in separation, distortion, and deformation of the separator and electrode, causing battery safety problems, and the breathability decreases when improving adhesiveness, making it difficult to thin the film.
A layer of inorganic particles with a thickness of 0.1 to 5 μm is formed on a porous substrate, and organic particles with multiple protrusions and valleys are added thereto to form an adhesive layer to ensure electrode adhesion and breathability, and by thermal pressure The machine extrudes and forms a diaphragm.
A separator with excellent electrode adhesion, adhesive resistance and breathability at a thin thickness is achieved, avoiding the problems of adhesive layer detachment and damage to battery performance, and ensuring the stability and safety of the battery.
Smart Images

Figure CN222338436U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to a secondary battery separator and an electrochemical element including the same, and more particularly to a secondary battery separator having excellent electrode adhesion, anti-adhesion and air permeability and an electrochemical element including the same. Background Art
[0002] In order to solve the high temperature stability problem of the separator, a ceramic coated separator (CCS) with a porous inorganic particle layer formed on one or both sides of a porous substrate has been used in the past. The ceramic coated separator has the advantage of excellent heat resistance due to its low high temperature heat shrinkage rate, so it is suitable for large battery systems for EVs.
[0003] However, the ceramic coating separators in the past had insufficient adhesion to the electrodes, so the separators and electrodes often separated during the battery cell assembly process, resulting in distortion and deformation of the electrode assembly. That is, as mentioned above, when the adhesion between the ceramic coating of the separator and the electrode is insufficient, misalignment occurs between the electrode and the separator in the jellyroll during cell stacking. When driving a stacked cell battery with misalignment as described above, local resistance occurs due to misalignment, or physical damage caused by continued use leads to a short circuit between the electrodes, so there are safety issues such as fire.
[0004] Therefore, improving the adhesion between the ceramic coating separator and the electrode is an issue that must be improved for battery stability.
[0005] As a method of improving the adhesion between the separator and the electrode, there is a method of forming an adhesive organic layer on the inorganic particle layer of the ceramic coating separator, but the air permeability is reduced due to the organic layer, making it difficult to form a thin film, and the electrode adhesion is still poor. In addition, when the separator is wound, the adhesive organic layer is separated from the adhesion phenomenon. Therefore, there are still problems that need to be solved, such as the reduction of the ionic conductivity of the separator and / or the occurrence of thickness deviation when aligning the electrode assembly, thereby hindering the performance of the battery.
[0006] [Prior art literature]
[0007] [Patent Literature]
[0008] (Patent Document 1) Japanese Patent Gazette No. 4414165 (Publication Date: 2005.03.03) Utility Model Content
[0009] Technical issues
[0010] In order to solve the above problems, an embodiment of the present invention aims to provide a separator having excellent electrode adhesion, anti-adhesion and air permeability even at a thin thickness, and an electrochemical element including the separator.
[0011] As one aspect, a membrane having an adhesive layer thickness of less than 2 μm and a total membrane thickness of less than 20 μm or less than 15 μm can be provided, with the aim of providing a membrane having excellent electrode adhesion, anti-adhesion and air permeability within the said range and an electrochemical element comprising the said membrane.
[0012] Technical Solution
[0013] As a solution for achieving the above-mentioned purpose, the utility model provides a secondary battery separator, comprising: a porous substrate having a thickness of 3 to 50 μm; an inorganic particle layer, which is arranged on at least one side of the porous substrate and has a thickness of 0.1 to 5 μm, and the inorganic particles are connected to each other to form pores between the inorganic particles; and an adhesive layer, which is arranged on the inorganic particle layer and has a thickness greater than 0 and less than 2 μm, and the organic particles having multiple protrusions (protrusion parts) and multiple valley parts (valley parts) are connected to each other to form pores.
[0014] In an implementation example, the ratio of the average particle size (D50) of the organic particles to the average particle size (D50) of the inorganic particles may be 0.5 to 3.
[0015] In one implementation example, the D50 of the organic particles may be 0.1 μm to 2 μm.
[0016] In one implementation example, D10 / D90 in the particle size distribution of the organic particles may be 0.3 to 0.9.
[0017] In one implementation example, the glass transition temperature (Tg) of the organic particles may be 50 to 90°C.
[0018] In one implementation example, the thickness of the adhesive layer may be greater than 0 μm and less than 2 μm.
[0019] In one implementation example, the organic particles may be secondary particles in which primary particles are mutually condensed by surface melting to form a plurality of protrusion parts and a plurality of valley parts, or primary particles having a plurality of protrusion parts and a plurality of valley parts on the surface.
[0020] In an implementation example, based on the total weight of the adhesive layer, the adhesive layer may contain more than 70 wt % of the organic particles.
[0021] In one implementation example, the adhesive layer may have a thickness of 0.2 to 2.0 g / m 2 Contains the organic particles.
[0022] In one implementation example, the secondary battery separator can have an electrode adhesion of 1.5 gf / 15 mm to 4.0 gf / 15 mm, wherein the electrode adhesion is measured by stacking the secondary battery separator on a carbon sheet (TOYO Tans o Korea, PF-20HP) having a thickness of 200 μm with the adhesive layer of the secondary battery separator facing the carbon sheet, and then bonding the membrane by pressing at 80°C and 20 MPa for 30 seconds using a hot press, and then peeling 180° using INSTRON's UTM equipment according to ASTM D 903.
[0023] In one implementation example, the secondary battery separator may be a separator having an air permeability change ΔG of 50 seconds / 100 cc or less as measured by the following formula.
[0024] △G=G1-G2
[0025] In the above formula, G1 is the Gurley permeability of a secondary battery separator having an inorganic particle layer and an adhesive layer stacked in sequence on both sides of a porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using a Densometer produced by Toyoseiki Co., Ltd. according to ASTM D 726, and the unit is seconds / 100cc.
[0026] In one implementation example, the secondary battery separator can be a separator in which two secondary battery separators are arranged with the adhesive layers facing each other, and then pressed at a temperature of 60°C and a pressure of 7.5 MPa for 1 hour. When peeled 180° according to ASTM D 903, the adhesive layers do not adhere to each other and are partially or completely peeled off, but are separated with the adhesive layers in their original state without adhesion.
[0027] Furthermore, as another solution for achieving the above-mentioned object, according to an implementation example of the present invention, an electrochemical element including the secondary battery separator of the above-mentioned implementation example is provided.
[0028] Technical Effects
[0029] The separator of the utility model can also have excellent electrode adhesion, anti-adhesion or air permeability at a thin thickness.
[0030] In one implementation example, the diaphragm can be a diaphragm stacked on a carbon sheet with a thickness of 200 μm and the adhesive layer of the diaphragm faces the carbon sheet, and then bonded by extruding at 80°C and 20 MPa for 30 seconds with a hot press, and the electrode adhesion measured by peeling 180° using a UTM device according to ASTM D 903 is 1.5 gf / 15 mm or more, 2.0 gf / 15 mm or more, 2.3 gf / 15 mm or more, 2.5 gf / 15 mm or more, or 3.0 gf / 15 mm or more. As an example, it can be a diaphragm of 1.5 gf / 15 mm to 4.0 gf / 15 mm. According to the implementation example, sufficient electrode adhesion can be ensured in the case of a relatively small amount of organic particles in the form of secondary particles in which the surface of the primary particles of the polymer having a high glass transition temperature is melted and condensed.
[0031] The separator of an implementation example can ensure excellent electrode adhesion even at a thin thickness, and can have excellent anti-adhesion properties. For example, after two separators stacked with a porous substrate-inorganic particle layer-adhesive layer are stacked and configured so that the adhesive layers face each other, they are pressed at a temperature of 60°C and a pressure of 7.5MPa for 1 hour. After that, the bonded part is peeled off, and SEM is used to confirm whether the adhesive layer is partially or completely peeled off to cause adhesion between the surfaces of the separators. In this case, adhesion as a phenomenon of the adhesive layer being separated from each other's separator parts does not occur, that is, it can have excellent anti-adhesion performance.
[0032] As an implementation example, the diaphragm can have excellent air permeability even if it has a multi-layer structure in which an adhesive layer is arranged on an inorganic particle layer. The air permeability change (△G) expressed by the following formula can be less than 50 seconds / 100cc, less than 40 seconds / 100cc, less than 35 seconds / 100cc or less than 30 seconds / 100cc.
[0033] △G=G1-G2
[0034] In the formula, G1 is the Gurley permeability of the diaphragm with an inorganic particle layer and an adhesive layer sequentially stacked on both sides of the porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using a Densometer of Toyoseiki Company according to ASTM D 726 specifications, and the unit is seconds / 100cc. In addition, the air permeability change can also be satisfied in the case of a diaphragm with an inorganic particle layer and an adhesive layer sequentially stacked on one side of the porous substrate.
[0035] The separator of one implementation example may be excellent in two or more of electrode adhesion, anti-adhesion and air permeability, and more preferably, may be excellent in electrode adhesion, anti-adhesion and air permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a photograph of the morphology of organic particles according to one aspect of the present invention observed by SEM;
[0037] Figure 2 The morphology of organic particles according to one aspect of the present invention is shown;
[0038] Figure 3 is a photograph of the adhesive layer of the separator of Example 1 observed by SEM;
[0039] Figure 4 This is a photograph of the adhesive layer of the separator of Comparative Example 1 observed by SEM;
[0040] Figure 5 This is a photograph of the adhesive layer of the separator of Comparative Example 2 observed by SEM;
[0041] Figure 6 This is a photograph of the adhesive layer of the separator of Comparative Example 3 observed by SEM;
[0042] Figure 7 is a cross-sectional view of a diaphragm according to one aspect of the utility model;
[0043] Figure 8 is a cross-sectional view of a diaphragm according to one aspect of the present invention.
[0044] Description of Reference Numerals
[0045] 100: Organic particles
[0046] 10: Protrusion
[0047] 20: Tanibe
[0048] 1: Porous substrate
[0049] 2: Inorganic particle layer
[0050] 3: Adhesive layer DETAILED DESCRIPTION
[0051] The present invention is described in more detail through the following implementation examples or embodiments. However, the following implementation examples of the present invention are only a reference for illustrating the present invention, and the present invention is not limited thereto and can be implemented in various ways.
[0052] Furthermore, the singular form used in the specification and technical solution may be intended to include the plural form unless otherwise specified in the text.
[0053] Furthermore, when it is mentioned that a part “includes” a certain constituent element, unless there is any particular description to the contrary, it does not exclude other constituent elements but indicates that other constituent elements may be included.
[0054] In the present invention, the organic particles 100 may be polymer particles, such as Figure 1 and Figure 2 As shown, it may be formed with a plurality of protrusions 10 and a plurality of valleys 20. As an example, the organic particles may be aggregates of a plurality of primary particles that are polymerized and condensed with each other through surface melting, i.e., secondary particles. The plurality of protrusions 10 and the plurality of valleys 20 may be formed by the condensation of the primary particles. The adhesive particles in the form of secondary particles may refer to a particle form having a plurality of protrusions corresponding to a portion of the primary particles, and a valley or a shrunken cavity formed between the protrusions and the protrusions. For example, it refers to a form of a plurality of protrusions (bump parts) of primary particle forms including three or more, four or more, five or more, six or more, or eight or more primary particles on the surface of the organic particles, and a plurality of valleys (valley parts) or shrunken cavities formed between the protrusions.
[0055] Alternatively, the primary particles may have a plurality of protrusions and a plurality of valleys on the surface.
[0056] The protrusions and valleys of the organic particles may be irregular in size and shape. The term "irregular" means substantially non-linear, substantially non-uniform, or substantially asymmetric. The term "protrusion" means a portion protruding from the surface of the particle. Figure 1 and Figure 2 The “valley or concave portion” refers to a concave portion (concavity) on the surface of the particle, which is formed by the height difference between the plurality of protrusions formed radially from the center of the organic particle, or a concave portion formed between protrusions, Figure 1 and Figure 2 In the figure, 20 is used to indicate it.
[0057] In the present utility model, "Dn" (n is a real number) refers to the diameter of particles whose cumulative fraction based on volume is equivalent to n%. For example, "D50" refers to the diameter of particles whose cumulative fraction based on volume is equivalent to 50%. "D90" refers to the diameter of particles whose cumulative fraction based on volume is equivalent to 90%. "D10" refers to the diameter of particles whose cumulative fraction based on volume is equivalent to 10%. The Dn can be derived from the particle size distribution results obtained by collecting samples of the particles to be measured according to ISO 13320-1 specifications and analyzing them using a particle size analyzer S3500 from Microtrac.
[0058] According to one aspect of the secondary battery diaphragm of the utility model, it can be a diaphragm including: a porous substrate; an inorganic particle layer arranged on at least one side of the porous substrate, in which inorganic particles are interconnected to form pores between the inorganic particles; and a diaphragm having an adhesive layer arranged on the inorganic particle layer, in which organic particles having multiple protrusions (protrusion parts) and multiple valleys (valley parts) are interconnected to form pores.
[0059] As an example, Figure 7 As shown in FIG. 1 , the porous substrate 1, the inorganic particle layer 2 and the adhesive layer 3 may be stacked in sequence. Figure 8 As shown, the adhesive layer 3, the inorganic particle layer 2, the porous substrate 1, the inorganic particle layer 2 and the adhesive layer 3 may be stacked in sequence. Figure 7 and Figure 8 The stacked structure of the secondary battery separator of the present invention is exemplified, but is not limited thereto.
[0060] Hereinafter, each structure of the secondary battery separator will be described in detail.
[0061] In one implementation example, the porous substrate may be a polyolefin-based porous substrate such as polyethylene and polypropylene, but is not particularly limited, and all porous substrates known as porous substrates for use as separators of electrochemical elements may be used. In one implementation example, the porous substrate may be manufactured into a film or a sheet, but is not particularly limited. As an example, the porous substrate includes polyolefins such as polyethylene and polypropylene, and a multilayer film of two or more layers may be used.
[0062] In one implementation example, the thickness of the porous substrate may be, for example, 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, or 6 μm or more. The upper limit is not particularly limited, but may be, for example, 100 μm or less, 50 μm or less, 30 μm or less, 20 μm or less, 15 μm or less, 12 μm or less, or a value between these values, and may be 1 to 100 μm without limitation, and may be 3 to 50 μm, 5 to 20 μm, or 5 to 15 μm in order to realize a high-capacity battery.
[0063] In one implementation example, the inorganic particle layer may include inorganic particles and an organic binder that interconnects the inorganic particles, and may be a porous inorganic particle layer in which the inorganic particles are connected and fixed by the organic binder to form pores between the inorganic particles. In one implementation example, the inorganic particle layer is disposed on one or both sides of a porous substrate, and may be coated to an area fraction of 60% or more, 70% or more, 80% or more, or 90% or more based on the entire surface of the porous substrate, preferably 100% except for some defective cases.
[0064] In one implementation example, the inorganic particle layer may be disposed on one or both sides of the porous substrate. When the inorganic particle layer is disposed on both sides of the porous substrate, the thickness of the inorganic particle layer disposed on one side and the other side may be the same or different.
[0065] In one implementation example, the thickness of the inorganic particle layer disposed on one side of the porous substrate may be greater than 0 μm, greater than 0.1 μm, greater than 0.2 μm, greater than 0.3 μm, greater than 0.4 μm, or greater than 0.5 μm, and may be less than 5 μm, less than 4 μm, less than 3 μm, less than 2 μm, or a value between the above values. Specifically, the thickness may be greater than 0 μm and less than 5 μm, 0.1 to 5 μm, 0.2 to 3 μm, or 0.5 to 2 μm, but is not limited thereto.
[0066] As an implementation example, the inorganic particles are added to improve the heat resistance of the diaphragm, and their types are not particularly limited. According to non-limiting examples, the inorganic particles may include one or more of metal hydroxides, metal oxides, metal nitrides and metal carbides. For example, it may include any one or more of the group consisting of SiO2, SiC, MgO, Y2O3, Al2O3, CeO2, CaO, ZnO, SrTiO3, ZrO2, TiO2 and AlO(OH), but not limited thereto. In order to improve the stability of the battery, the inorganic particles are more preferably metal hydroxide particles such as boehmite, pseudo-boehmite, aluminum hydroxide and magnesium hydroxide, but not limited thereto.
[0067] As an implementation example, when boehmite is used as the inorganic particle, the specific surface area (BET) of the boehmite may be 10 m 2 / g or above or 15m 2 / g or more, but is not particularly limited thereto.
[0068] In one implementation example, the D50 of the inorganic particles may be greater than 0 μm, greater than 0.05 μm, greater than 0.1 μm, less than 5 μm, less than 3 μm, less than 2 μm, less than 1 μm, less than 0.5 μm, or a value between the above values. For example, it may be greater than 0 μm and less than 5 μm, or greater than 0 μm and less than 3 μm, greater than 0.05 μm and less than 2 μm, greater than 0.1 μm and less than 1 μm, or greater than 0.1 μm and less than 0.5 μm.
[0069] In one implementation example, the type of the organic binder of the inorganic particle layer is not limited as long as it is a porous inorganic particle layer that can connect and fix the inorganic particles to form a space between the inorganic particles. As an example, the organic binder can be in a particle form or a non-particle form. In the case of a particle form, it can be a particle of a different form from the organic particles having the plurality of protrusion parts and the plurality of valley parts. In addition, the organic binder can be an aqueous latex.
[0070] Regarding the organic binder, for example, non-limiting examples may include acrylic polymers selected from polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, etc.; (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, (3-glycidyloxypropyl)trimethoxysilane and their oligomers or silane compounds prepared therefrom; styrene butadiene rubber; carboxylmethylcellulose (CMC); polyvinylidene fluoride (PVDF); any one or two or more selected from the group consisting of polyvinyl fluoride (PVdF); polyvinyl pyrrolidone (PVP); and polyvinylacetate (PVAc); etc., but the present invention is not limited thereto.
[0071] The organic binder may be used in an amount of 0.1 to 30 parts by weight, 0.2 to 10 parts by weight, or 0.2 to 5 parts by weight based on 100 parts by weight of the inorganic particles, but is not limited thereto.
[0072] The inorganic particle layer is manufactured by the conventional manufacturing method that the inorganic particle layer is configured on the porous substrate as known in the corresponding technical field, and is not particularly limited. As a non-limiting example, after preparing the slurry of water or organic solution containing the inorganic particles and organic binder, one or a combination of methods such as slot die coating, roll coating, spin coating, dip coating, bar coating, die coating, slit coating and inkjet printing can be coated on one or both sides of the porous substrate to form the inorganic particle layer on the porous substrate.
[0073] Next, the adhesive layer of this embodiment and the organic particles forming the adhesive layer will be described in detail.
[0074] In the utility model, the adhesive layer is coated with Figure 1 and Figure 2 The porous layer formed by the composition of organic particles of the morphology shown in the figure, by including the organic particles of the specific morphology, has excellent adhesion to the electrode in the case of a thin film, specifically, in the case of a thickness of less than 20 μm, and the increase in the transmittance after forming the adhesive layer is still small compared to the transmittance of the porous substrate itself, and no adhesion occurs, so that the problem occurring when assembling the battery can be solved. In addition, a separator having better adhesion to the electrode than using generally spherical organic particles can be provided.
[0075] The organic particles may be secondary particles in the form of primary particles condensed by surface melting or single particles having a plurality of protrusions and a plurality of depressions or valleys between the protrusions.
[0076] The organic particles are not particularly limited, but may be, for example, "organic particles in the form of secondary particles" having a D50 particle size of 0.1 to 1.5 μm, 0.2 to 1.5 μm, or 0.3 to 1 μm. Typical forms of the binder particles in the form of secondary particles are as follows: Figure 1As shown, it may refer to a plurality of polymerized primary particles that melt with each other, for example, the surface melts to agglomerate, so that the primary particles protrude on the surface of the agglomerate and valleys are formed between the primary particles. As another example, it may refer to a particle having three or more protruding protrusions and multiple valleys or multiple shrunken cavities between the protrusions in one particle even without agglomeration. For example, it may refer to a particle having three or more, four or more, five or more, or six or more protruding protrusions and multiple valleys or multiple shrunken cavities between the protrusions formed on the surface of an organic particle.
[0077] The organic particles of the present invention having the size and shape are as follows Figure 5 Compared with spherical organic particles of the morphology shown, even if the content is relatively small, the adhesion between the electrode can be sufficiently improved and the air permeability and anti-blocking property can be significantly improved.
[0078] And regarding the average particle size (D50) of the organic particles, there is no special restriction on the premise of having the above-mentioned morphology, but for example, it can be less than 10μm, less than 5μm, less than 2μm, less than 1μm, less than 0.5μm, more than 0.1μm, more than 0.3μm, more than 0.5μm, preferably, it can be 0.1 to 10μm, more preferably, it can be 0.1 to 2μm, it can be 0.1 to 1.5μm, and very preferably, it can be 0.2 to 1.0μm.
[0079] In the case of the average particle size range, the adhesion effect with the inorganic particles is better achieved and the adhesion with the electrode is significantly improved. In particular, in the case of a size of 0.1 to 1.5 μm, the adhesion between the adhesive layers during transfer or lamination, or the adhesion of the adhesive to other parts in contact with the adhesive layer, resulting in the detachment of the adhesive layer on the inorganic particle layer, is significantly reduced, the adhesion with the electrode is also significantly increased, and it can be made into a thin film, which is better.
[0080] In one implementation example, regarding the particle size distribution of the organic particles, the D10 / D90 value may be greater than 0.3, greater than 0.4, less than 0.9, less than 0.8, or a value between the above values. Alternatively, it may be 0.3 to 0.9, or 0.4 to 0.8. When the particle size distribution range of the organic particles is met, the content of the organic particles used to ensure the electrode adhesion can be further reduced, thereby being more conducive to ensuring air permeability and anti-adhesion, and therefore preferred, but not necessarily limited thereto.
[0081] In one implementation example, for the organic particles, the ratio of the average particle size of the organic particles to the average particle size (D50) of the inorganic particles is 0.5 or more, 0.6 or more, 0.7 or more, 3 or less, 1.7 or less, 1.5 or less, 1.3 or less, 1.0 or less, or a value between the above values. The content of organic particles flowing into the surface unevenness or pores of the inorganic particle layer can be further reduced, so as to be more conducive to ensuring air permeability and anti-adhesion, and therefore it is preferred, but not necessarily limited thereto. Preferably, the average diameter of the organic particles / the average diameter ratio of the inorganic particles can be 0.5 to 3.0, 0.5 to 2.0, 0.5 to 1.7, 0.5 to 1.5, 0.6 to 1.3, or 0.7 to 1.0.
[0082] As an implementation example, the adhesive layer may contain 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 99% by weight or more, or 100% organic particles based on the total weight of the adhesive layer in order to provide a thin-thickness separator having excellent electrode adhesion, anti-adhesion and air permeability. The more organic particles in the form of secondary particles, the more conducive it is to achieving the purpose of the utility model, so there is no particular limit on the upper limit of the content.
[0083] According to one implementation example, the organic particles constituting the adhesive layer formed on the inorganic particle layer in the separator are as follows: Figure 1 As shown, it has a specific morphology as defined above, so compared with the polymer that is the same as the organic particles but has a morphology as shown Figure 5 The spherical or round shape without valleys can have relatively significant electrode adhesion, air permeability, anti-adhesion and other excellent physical properties. Therefore, the composition of the organic particles of the utility model is not particularly limited, as long as it is the composition of organic particles commonly used in the corresponding technical field to improve electrode adhesion.
[0084] For example, the organic particles may be made of crosslinked or uncrosslinked particle-type acrylic polymer or fluorine-based polymer, or may be of a core-shell structure. The core-shell structured particle-type acrylic polymer may be, for example, a core rubber or crosslinked particle surface including acrylic monomers and other comonomers and crosslinking agents as required to polymerize, but is not particularly limited.
[0085] The organic particles of the specific form according to the implementation example are preferably used because of their structural characteristics, so that a small amount can significantly improve the electrode adhesion, and the case of having a high glass transition temperature can further improve the anti-adhesion property. In this case, the glass transition temperature (Tg) of the organic particles can be above 50°C, above 60°C, below 90°C, below 80°C, below 70°C, or a value between these values, for example, 50 to 90°C, 55 to 75°C, or 60 to 70°C, but is not limited thereto.
[0086] In one implementation example, in addition to the organic particles, the adhesive layer may selectively further include other components such as lubricants and surfactants that are known to be added to the electrode adhesive organic layer of the separator in the corresponding technical field, but is not particularly limited.
[0087] In one implementation example, the adhesive layer is a porous particle layer in which the organic particles are connected and fixed to each other. Based on the total surface of the inorganic particle layer, the area fraction can be 60% or more, 70% or more, 80% or more, or 100%. Except for special defects, 100% can be laminated. In one implementation example, the air permeability and ion conductivity of the diaphragm can be further improved by forming a porous inorganic particle layer on a porous substrate and then laminating a porous adhesive layer of the above-mentioned shape and size on the porous inorganic particle layer, but it is not particularly limited.
[0088] In one implementation example, the thickness of the adhesive layer may be greater than 0 μm, greater than 0.1 μm, greater than 0.2 μm, greater than 0.3 μm, less than 2 μm, less than 1.5 μm, less than 1 μm, less than 0.9 μm, less than 0.7 μm, or a value between these values. The thickness of the adhesive layer may be greater than 0 μm and less than 2 μm. In order to achieve a high-capacity battery, it may be 0.1 to 1 μm.
[0089] In one implementation example, the total thickness of the separator having an inorganic particle layer and an adhesive layer respectively arranged on one or both sides of the porous substrate can be 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, 30 μm or more, 50 μm or less, 30 μm or less, 20 μm or less, 15 μm or less, or values between the above values. The total thickness of the separator can be 5 to 50 μm, and in order to realize a high-capacity battery, it can be 5 to 25 μm, or 7 to 20 μm, but is not particularly limited.
[0090] In one implementation example, the content of organic particles in the adhesive layer may be 0.2 g / m 2 Above, 0.5g / m 2 Above, 1g / m 2 Above, 2.0g / m2 Below, 1g / m 2 Below, 0.5g / m 2 The value below or between these values, preferably, can be 0.2 to 1.0 g / m 2 .
[0091] There is no particular restriction on the method for manufacturing the organic particles of the specific form. However, in one implementation example, a polymerization solution of primary particles can be prepared using various free radical polymerization monomers such as acrylic acid or fluorine by polymerization methods such as emulsion polymerization and suspension polymerization, and then spray-dried at a high temperature of 200°C to 300°C for several seconds and then classified by size to produce a coagulation form in the form of secondary particles. Alternatively, suspension polymerization can be performed and then vacuum distillation can be performed to remove non-polymerizable monomers from the polymer particles to form protrusions and valleys, but it is not limited to this.
[0092] The adhesive layer can be configured on the inorganic particle layer by all methods known in the corresponding technical field, and the scheme is not particularly limited. As a non-limiting example, after the organic particles are added with water and stirred to prepare a slurry for the adhesive layer, the prepared slurry can be coated on the inorganic particle layer by one or a combination of slot die coating, roller coating, spin coating, dip coating, rod coating, pattern coating, slit coating, inkjet printing, and dried to configure the adhesive layer on the inorganic particle layer.
[0093] In one implementation example, the separator may be a separator laminated on a carbon sheet having a thickness of 200 μm with the adhesive layer of the separator facing the carbon sheet, and then bonded by pressing at 80°C and 20 MPa for 30 seconds using a hot press, and the electrode adhesion measured by peeling 180° using a UTM device according to ASTM D 903 is 1.5 gf / 15 mm or more, 2.0 gf / 15 mm or more, 2.5 gf / 15 mm or more, or 3 gf / 15 mm or more. Alternatively, the separator may be 1.5 gf / 15 mm to 4.0 gf / 15 mm, or 2.0 to 4.0 gf / 15 mm.
[0094] According to the implementation example, even if a small amount of organic particles having the above-mentioned morphology and a high glass transition temperature are used to apply thinly or the coating area is insufficient, the distribution is good. Therefore, when coated on an inorganic particle layer, sufficient electrode adhesion can be ensured while improving anti-adhesion properties, which is more preferred.
[0095] For example, excellent anti-adhesion properties can be ensured as described below, that is, after two diaphragms in which a porous substrate, an inorganic particle layer and an adhesive layer are stacked in sequence are arranged so that the adhesive layers face each other, it is confirmed by SEM that when the two diaphragms are pressed at a temperature of 60°C and a pressure of 7.5 MPa for 1 hour and then separated, whether the adhesive layer is partially or completely peeled off, causing adhesion between the surfaces of the diaphragms, and no adhesion occurs.
[0096] The air permeability change (ΔG) of the separator of one implementation example expressed by the following formula may be 50 sec / 100cc or less, 45 sec / 100cc or less, 40 sec / 100cc or less, 35 sec / 100cc or less, or 30 sec / 100cc or less.
[0097] △G=G1-G2
[0098] In the above formula, G1 is the Gurley permeability of the separator having an inorganic particle layer and an adhesive layer sequentially stacked on both sides of the porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using a Densometer of Toyoseiki Co., Ltd. according to ASTM D 726, and the unit is seconds / 100cc.
[0099] The separator according to an implementation example may be excellent in two or more of electrode adhesion, anti-adhesion and air permeability, and more preferably, may be excellent in electrode adhesion, anti-adhesion and air permeability.
[0100] Another implementation example provides an electrochemical element including the diaphragm. The electrochemical element may be an energy storage device, which is not particularly limited, but a lithium secondary battery may be cited as a non-limiting example. The lithium secondary battery is well known and its structure is also known, so it is not described in detail in the present utility model.
[0101] According to an implementation example, a lithium secondary battery may be a battery including the above-mentioned separator between a positive electrode and a negative electrode. Here, the positive electrode and the negative electrode may be used without restriction as long as they are positive electrodes and negative electrodes commonly used in lithium secondary batteries.
[0102] The present invention is described in more detail below based on the following embodiments and comparative examples. However, the following embodiments and comparative examples are only used to illustrate the present invention in more detail, and the present invention is not limited to the following embodiments and comparative examples.
[0103] The following are the methods for measuring the physical properties of the separator.
[0104] 1. Electrode adhesion
[0105] The separator was stacked on a 200 μm thick carbon sheet (TOYO Tanso Korea, PF-20HP) with the adhesive layer of the separator facing the carbon sheet, and then pressed at 80°C and 20 MPa for 30 seconds using a hot press to bond the separator. The electrode adhesive strength was measured by peeling 180° using the UTM equipment of INSTRON according to ASTM D 903. If the adhesive strength of the adhesive layer of the separator was too low to be peeled even using the UTM equipment, it was rated as "unmeasurable".
[0106] 2. Change in air permeability
[0107] The air permeability change ΔG is calculated as follows.
[0108] △G=G1-G2
[0109] In the above formula, G1 is the Gurley permeability of the membrane with the inorganic particle layer and the adhesive layer sequentially stacked on both sides of the porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using a Densometer of Toyoseiki Co., Ltd. according to ASTM D 726 specifications, and the time required for 100cc of air to pass through a membrane with an area of 1 square inch is recorded in seconds. The unit is seconds / 100cc.
[0110] 3. Anti-blocking
[0111] After configuring the two diaphragms stacked with a porous substrate-inorganic particle layer-adhesive layer so that the adhesive layers face each other, they are pressed at a temperature of 60°C and a pressure of 7.5MPa for 1 hour. Afterwards, the phenomenon of partial or complete peeling of the adhesive layers caused by mutual adhesion when peeled 180° is evaluated according to ASTM D 903. Even if partial peeling occurs, it is considered that adhesion has occurred. If no peeling occurs, it is considered that no adhesion occurs when the adhesive layers are separated in their original state. Confirm whether adhesion has occurred by SEM. If adhesion is confirmed by SEM, it is rated as 'NG', and if adhesion is not confirmed, it is rated as 'OK'.
[0112] 4.Method for measuring average particle size
[0113] The average particle size (D50), D10, and D90 were measured using a particle size analyzer S3500 manufactured by Microtrac according to ISO 13320-1.
[0114] 5. Glass transition temperature
[0115] The glass transition temperature was measured as follows: using a DSC device (model name: Q200) from TA Corporation, the temperature was raised from -50°C to 300°C at a heating rate of 20°C / min in a nitrogen atmosphere. At this time, the measurement was performed by heating twice (first run, second run, cooling).
[0116] [Example 1]
[0117] 1) Preparation of slurry for adhesive layer
[0118] Will be as Figure 1 An acrylic latex (acrylic latex obtained by polymerizing methyl methacrylate and butyl methacrylate) having an average particle size (D50) of 550 nm and a glass transition temperature (Tg) of 65° C. of organic particles of the form shown was added to water so as to have a solid content of 5 wt % and stirred to prepare a uniformly mixed adhesive layer slurry. Here, D10 / D90 of the organic particles was 0.57.
[0119] 2) Preparation of slurry for inorganic particle layer
[0120] 100 parts by weight of boehmite particles (Nabaltec, Apyral AOH60) with a D50 of 600 nm as inorganic particles were mixed with 3 parts by weight of a water-soluble acrylic binder (Ashland, PVP K120) and water to prepare a slurry containing 40% by weight of inorganic particles.
[0121] 3) Manufacturing of diaphragm
[0122] The inorganic particle layer slurry was coated on both sides of a polyolefin porous substrate (ENPASS, SK innovation) having a Gurley transmittance of 125 seconds / 100cc and a thickness of 8.5 μm using two slot die coating dies and fully dried at 40°C to form an inorganic particle layer. Thereafter, the adhesive layer slurry was coated on the upper surface of the inorganic particle layer and fully dried at 40°C to form an adhesive layer. The thickness of the inorganic particle layer of the diaphragm was 1.5 μm and the thickness of the adhesive layer was 0.5 μm, and the total thickness of the diaphragm was 12.5 μm. The content of organic particles in the coated adhesive layer was 0.4 g / m 2 . Figure 3 The surface photographs of the adhesive layer are included, and the physical properties thereof are described in Table 1.
[0123] [Example 2]
[0124] A separator was produced in the same manner as in Example 1 except that D50 was 400 nm when preparing the adhesive layer slurry. The results are shown in Table 1.
[0125] [Example 3]
[0126] A separator was produced under the same conditions as in Example 1 except that the acrylic latex having a D50 of 1.8 μm and a glass transition temperature (Tg) of 65° C. was applied in the amount described in Table 1 as the composition of the organic particles of Example 1. Table 1 shows the results.
[0127] [Example 4]
[0128] A separator was produced under the same conditions as in Example 1 except that the adhesive layer slurry was prepared with the same composition as in Example 1 and an acrylic latex having a D50 of 1.0 μm and a glass transition temperature (Tg) of 62° C. was applied in the amount described in Table 1. The results are shown in Table 1.
[0129] [Comparative Example 1]
[0130] The same method was used except that the acrylic latex of Example 1 was dissolved in an organic solution and applied to the inorganic particle layer. Figure 4 The results are shown in Table 1.
[0131] [Comparative Example 2]
[0132] The organic particles of Example 1 were replaced with completely spherical organic particles prepared by suspension polymerization using the same monomers as in Example 1. Figure 5 A separator was manufactured under the same conditions as in Example 1 except that an acrylic latex having a spherical shape and a D50 of 540 nm and a glass transition temperature (Tg) of 65° C. was applied in the amount described in Table 1. Figure 5 The results are listed in Table 1.
[0133] [Comparative Example 3]
[0134] A separator was manufactured under the same conditions as in Example 1 except that the organic particles in Example 1 were replaced with acrylic latex having a D50 of 200 nm and a glass transition temperature (Tg) of 65°C as completely spherical organic particles and were applied in the amount described in Table 1. Figure 6 The results are listed in Table 1.
[0135] Table 1 below summarizes the evaluation results of the physical properties of the separators manufactured in the examples and comparative examples of the present invention.
[0136]
Table 1
[0137]
[0138] Referring to the results and figures in Table 1, it can be confirmed that the adhesive layer Figure 3In the cases of Examples 1 and 2, which are formed by organic particles having a secondary particle morphology including raised protrusions and valley parts between the protrusions on the surface, and in which the average particle size ratio of the organic particles to the inorganic particles is between 0.5 and 1.5 and the average particle size of the organic particles is less than 1.5 μm, an adhesive layer with the best electrode adhesion and anti-adhesion properties is well formed on the inorganic particle layer.
[0139] Furthermore, it can be seen that in the case of Example 4, in which the average size of the organic particles is 1 μm and the ratio of organic particles to inorganic particles is 1.67, the electrode adhesion and anti-adhesion properties are worse than those of Examples 1 and 2 but significantly better than those of the comparative example. It can be seen that in the case of Example 3, in which the average size is 1.8 μm and the ratio of organic particles to inorganic particles is 3, although the anti-adhesion properties are inferior to those of Examples 1, 2 and 4, it exhibits excellent adhesion compared with the comparative example.
[0140] In contrast, Comparative Example 1 uses a soluble acrylic polymer such as Figure 4 The pores on the surface are blocked, so the air permeability is poor and the electrode bonding force is also extremely low. In the case of Comparative Examples 2 and 3 having a spherical bonding layer, Figure 5 and Figure 6 As shown, the bonding layer is spherical, in which case the electrode bonding is poor and the anti-blocking property is extremely poor.
[0141] As described above, the present invention is described through specific matters and limited embodiments, but this is only provided to help fully understand the present invention. The present invention is not limited to the above embodiments, and ordinary technicians in the field to which the present invention belongs can make various modifications and variations based on these records.
[0142] Therefore, the present invention should not be limited to the embodiments described above, and the above technical solutions and everything that is equivalent to or has equivalent variations of the technical solutions belong to the scope of the present invention.
Claims
1. A secondary battery separator, characterized in that: include: A porous substrate having a thickness of 3 to 50 μm; an inorganic particle layer disposed on at least one side of the porous substrate and having a thickness of 0.1 to 5 μm, wherein the inorganic particles are interconnected to form pores between the inorganic particles; and The adhesive layer is disposed on the inorganic particle layer and has a thickness of more than 0 and less than 2 μm. The organic particles having a plurality of protrusions and a plurality of valleys are connected to each other to form pores.
2. The secondary battery separator according to claim 1, characterized in that: The ratio of the average particle size D50 of the organic particles to the average particle size D50 of the inorganic particles is 0.5 to 3.
3. The secondary battery separator according to claim 1, characterized in that: The organic particles have a D50 of 0.1 to 2 μm.
4. The secondary battery separator according to claim 1, characterized in that: The particle size distribution D10 / D90 of the organic particles is 0.3 to 0.
9.
5. The secondary battery separator according to claim 1, characterized in that: The organic particles have a glass transition temperature Tg of 50 to 90°C.
6. The secondary battery separator according to claim 1, characterized in that: The organic particles are secondary particles formed by mutual agglomeration of primary particles through surface melting to form a plurality of protrusions and a plurality of valleys, or are primary particles having a plurality of protrusions and a plurality of valleys on the surface.
7. The secondary battery separator according to claim 1, characterized in that: The adhesive layer contains 70 wt % or more of the organic particles based on the total weight of the adhesive layer.
8. The secondary battery separator according to claim 1, characterized in that: The adhesive layer has a thickness of 0.2 to 2.0 g / m 2 Contains the organic particles.
9. The secondary battery separator according to claim 1, characterized in that: The secondary battery separator is a secondary battery separator with an electrode adhesion of 1.5 gf / 15 mm to 4.0 gf / 15 mm, wherein the electrode adhesion is measured by laminating the secondary battery separator on a carbon sheet with a thickness of 200 μm with the adhesive layer of the secondary battery separator facing the carbon sheet, and then bonding the membrane by pressing at 80°C and 20 MPa for 30 seconds with a hot press, and then peeling 180° using the UTM equipment of INSTRON according to ASTM D 903.
10. The secondary battery separator according to claim 9, characterized in that: The secondary battery separator has an air permeability change ΔG measured by the following formula of 50 seconds / 100cc or less, ΔG=G1-G2 In the above formula, G1 is the Gurley permeability of a secondary battery separator having an inorganic particle layer and an adhesive layer stacked in sequence on both sides of a porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using an air permeability meter produced by Toyoseiki Co., Ltd. according to ASTM D 726 specifications, and the unit is seconds / 100cc.
11. The secondary battery separator according to claim 10, characterized in that: The secondary battery separator is a secondary battery separator in which two secondary battery separators are arranged so that the adhesive layers face each other, and then pressed at a temperature of 60°C and a pressure of 7.5 MPa for 1 hour. When peeled 180° according to ASTM D903, the adhesive layers do not adhere to each other and partially or completely peel off, but are separated in their original state without adhesion.
12. An electrochemical element, characterized in that: A secondary battery separator selected from any one of claims 1 to 11.